High thermal radiation of Ca-doped lanthanum chromite1. Issue 39 (2nd May 2015) - Lu, Yi; Fang, Zhenggang; Lu, Chunhua; Wei, Ling; Ni, Yaru; Xu, Zhongzi; Tao, Shunyan
<x xml:space="preserve">Abstract</x> The graph describes the preparation process and characterization methods, as well as applications of samples.